Image of critical care nursing in Spain as seen by Central European patients : an approach towards the identity of Spanish care professionals in the context of the European Union - Manuel Lillo Crespo; Isabel Casabona Martínez; Roberto Galao Malo; María Dolores Mora Antón (Universidad de Alicante, 2012)
During the last few years, there has been an increase of citizens from central and northern Europe along the Spanish Mediterranean coastline, either as residents or as tourists (who can also be admitted to hospital). Specifically in the Alicante province, a growing number of Scandinavians can be found in the Marina Alta County, and English people in Torrevieja. The chosen group for our study comprises mostly Dutch people. They are retired and mean age is older than 60. For age and health reasons, they tend to make a frequent use of the Spanish health care system (mostly private); that is why it is interesting to find out their opinion on health care professionals in Spain, in order to establish a comparison with other European countries (in this case, their own) within the professional context of the European union. In general, Spanish nurses excelled most of these patients' expectancies. A nursing professional profile could be therefore established as: reliable, empathic and communicative -in spite of the language barrier-; self-confident towards their job and transmitting security to patients accordingly; capable of a quick response, of giving an opinion and problem-solving; respectful with intimacy although somewhat distant when carrying out procedures affecting privacy.